(untitled) (Journal of Asian Development Studies, 2025)
This study examines Second Language Acquisition (SLA) and assessment practices among English Language Teaching (ELT) learners at NUML Peshawar, with a focus on CEFR levels A1, B1, and C1. The research examines how learners at these distinct levels experience and respond to SLA methods, as well as how assessment tools integrate with their linguistic capabilities. Drawing on case-based analysis, the study presents 30 detailed learner profiles and analyses their progression through SLA processes. The methodology comprises qualitative interviews, classroom observations, and performance assessments, which are analysed using thematic and comparative approaches. Data reveal key pedagogical and institutional challenges, highlighting the importance of contextualized instruction and appropriate assessment methods. The study also argues that CEFR standards can be more effectively implemented to support learner outcomes. By proposing practical implications for curriculum designers, language instructors, and policymakers, the research contributes to ongoing discussions on effective SLA and fair, level specific assessment. This article gives a conclusion with suggestions for promoting learner centred teaching and aligning teaching methods with CEFR objectives. The article is a valuable contribution to the expanding body of evidence for research-based enhancements in ELT programs in Pakistani higher education settings. The study concludes by providing recommendations for SLA-based curriculum development, along with instructor development strategies, and the impact of the CEFR on creating fair and efficient assessment frameworks.